The Effect of Transformational Leadership on Organizational Commitment Mediated by Job Satisfaction of Employees of PT PLN (Persero) Lampung Distribution Main Unit - Refa James SIMATUPANG (International Journal of Environmental, Sustainability, and Social Science, 2021)
The problem in this study is that employees at PT PLN (Persero) Lampung Main Unit have low organizational commitment. Other issues include the workplace atmosphere, the presence of leadership in the Distribution Parent Unit of PT PLN (Persero) Lampung, the presence of employees at work, and the transformational leadership that has been operating at the Distribution Parent Unit of PT PLN (Persero) Lampung but has not been implemented effectively. Job satisfaction of workers at PT PLN (Persero) Lampung Distribution Main Unit is used as a proxy for an organizational commitment that has an impact on transformational leadership. As many as 22 employees of PT PLN (Persero) Lampung Distribution Main Unit became the research population. The Lampung Main Distribution Unit, PT PLN (Persero) Lampung, provided a sample of 69 employees for this study, which was conducted using a quantitative methodology. Based on the analysis results, transformational leadership has a positive and substantial effect on organizational commitment, has a positive and significant effect on job satisfaction, and has an effect on organizational commitment mediated by job satisfaction.